2017
DOI: 10.3201/eid2312.171062
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Reassorted Viruses as Cause of Highly Pathogenic Avian Influenza A(H5N8) Virus Epidemic, the Netherlands, 2016

Abstract: In 2016, an epidemic of highly pathogenic avian influenza A virus subtype H5N8 in the Netherlands caused mass deaths among wild birds, and several commercial poultry farms and captive bird holdings were affected. We performed complete genome sequencing to study the relationship between the wild bird and poultry viruses. Phylogenetic analysis showed that the viruses are related to H5 clade 2.3.4.4 viruses detected in Russia in May 2016 but contained novel polymerase basic 2 and nucleoprotein gene segments and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
106
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(121 citation statements)
references
References 22 publications
8
106
0
Order By: Relevance
“…However for the H5N8 2014 group A virus, no mortality was observed in the wild bird population. We previously showed that the pathogenicity of the three viruses for galliform birds was similar, for all viruses an IVPI score of 3.0 was measured (Beerens et al., , ; Bouwstra, Heutink, et al., ). In this study, we performed an IVPI experiment using ducks.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…However for the H5N8 2014 group A virus, no mortality was observed in the wild bird population. We previously showed that the pathogenicity of the three viruses for galliform birds was similar, for all viruses an IVPI score of 3.0 was measured (Beerens et al., , ; Bouwstra, Heutink, et al., ). In this study, we performed an IVPI experiment using ducks.…”
Section: Discussionmentioning
confidence: 85%
“…Briefly, purified amplicons were sequenced at high coverage (average >1000 per nucleotide position) using the Nextera library preparation method and Illumina MiSeq paired‐end 150 base pairs sequencing. Quality control‐passed sequence reads were mapped using the ViralProfiler‐Workflow, an extension of the CLC Genomics Workbench (Qiagen, Germany), as previously described (Beerens et al., ). The consensus sequences generated in this study were submitted to the GISAID database.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…H5N8 virus had not previously been widely seen in Europe, and the risk for bird-to-human transmission was not clear. Avian outbreaks increased in number, size, and distribution among migratory and resident birds, zoo birds, backyard farms, and poultry holdings, to a scale not previously observed for a subtype during a winter season ( 23 , 24 ). Overall, 24 of the 31 the European Union/European Economic Area (EU/EEA) countries, neighboring countries, Israel, and countries in the Middle East were facing large avian influenza outbreaks in poultry or wild birds during the study period, and there was great uncertainty about the risk for virus transmission from birds to humans ( 25 ).…”
mentioning
confidence: 74%
“…This time lag might be related to the limited mobility of wintering Aythya ducks, which, in contrast to Eurasian wigeons, rarely fly over land between foraging and roosting sites. Wild bird ecology might thus affect infection risk among poultry, which was further explored by researchers using network analyses of virus sequences obtained from wild birds and poultry during the same outbreak ( 14 ). …”
Section: The Studymentioning
confidence: 99%